A comprehensive real‐time state evaluation strategy for distribution equipment based on MI‐PSO‐BP algorithm - Zhichun, Yang; Yu, Shen; Fan, Yang; Zilin, Wan; Jian, Le (International transactions on electrical energy systems, 2019)
Summary This paper studies a comprehensive state assessment strategy for distribution equipment with the aim to enhance the reliability and real‐time performance of the state evaluation. In an implementation framework of two‐stage evaluation, a qualitative assessment method is employed to carry out the initial state evaluation, in order to provide sufficient training data samples for the real‐time evaluation in the second stage. To improve the accuracy and timelessness of the distribution equipment state evaluation, we use a mutual information‐based technology to refine the training data set and apply particle swarm optimization approach to optimize the parameters of the neural network‐based prediction model that is crucial to the real‐time evaluation. Numerical simulation results are provided to demonstrate the performance of the developed strategy.